2018
DOI: 10.3389/fcimb.2018.00293
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Listeria monocytogenes Virulence by Cannabis sativa L. Essential Oil

Abstract: Anti-virulence strategies are being explored as a novel approach to combat pathogens. Such strategies include inhibition of surface adhesion, tissue invasion, toxin production, and/or interference with the gene regulation of other virulence traits. Listeria monocytogenes, the causative agent of listeriosis, is a facultative intracellular food pathogen characterized by a wide distribution in the environment. Its ability to persist within biofilms and to develop resistance to sanitizers is the cause of significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 41 publications
(46 reference statements)
5
35
0
1
Order By: Relevance
“…The ability of a sublethal concentration (256 μg/mL) of Cannabis sativa L. essential oil extracted from the French monoecious variety Futura 75 to attenuate the virulence of eleven L. monocytogenes strains isolated from patients diagnosed with invasive listeriosis has been evaluated by a survival experiment. After 6 days of infection survival rates of infected groups compared with those who were not infected increased remarkably (from 50 to 90%) [72].…”
Section: Listeria Monocytogenes (L Monocytogenes)mentioning
confidence: 95%
“…The ability of a sublethal concentration (256 μg/mL) of Cannabis sativa L. essential oil extracted from the French monoecious variety Futura 75 to attenuate the virulence of eleven L. monocytogenes strains isolated from patients diagnosed with invasive listeriosis has been evaluated by a survival experiment. After 6 days of infection survival rates of infected groups compared with those who were not infected increased remarkably (from 50 to 90%) [72].…”
Section: Listeria Monocytogenes (L Monocytogenes)mentioning
confidence: 95%
“…It has recently been described that Granzyme B seriously impairs L. monocytogenes infection by degrading Listeriolysin O (LLO) which is one of the majors virulent factors activated by PrfA [43]. A recently published report also supports this thesis where steam-distilled essential oil of Cannabis sativa was shown to down-regulate PrfA [45]. In the mentioned work the ability of L monocytogenes to invade Caco-2 cells was significantly reduced in the presence of the essential oil and infected Galleria mellanella larvae in the presence of the essential oil presented higher survival rates than the corresponding control experiments [45].…”
Section: Discussionmentioning
confidence: 78%
“…Some studies indicated that the essential oils have antimicrobial activity against many pathogens, regarding bacteria, as well as fungi (Ferronatto et al, 2007;Santurio et al, 2011). Marini et al (2018), tested the antimicrobial activity of the essential oil of Cannabis sativa against Listeria monocytogenes, and obtained the MBC ≥ 2.048 mg/mL, thus suggested bactericidal activity due to the presence of the identified main compounds of the oil, myrcene and α-pinene. These two substances could also be identified in the present study, specifically the α-pinene in both oils (EOA and EOO) and the myrcene only in the EOO.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…L. monocytogenes is known to cause the disease listeriosis, which affects principally immunocompromised patients, thereby having a mortality rate of 30%. Furthermore, the bacteria bear the ability for biofilm formation, and by this way developing resistance to sanitizers and antimicrobial agents, thus provoking serious problems to food industries (Oliveira et al, 2016b;Rogalla and Bomar, 2018;Marini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%